Effect on Intestinal Flora of Long-term Ingestion of a Novel Supplement Containing Lactic Acid Bacteria Isolated from the Tonewase Persimmon - GOTOH, Akinobu; MATSUNAGA, Wataru (Chōnai saikingaku zasshi, 2021)
Human intestinal flora plays an important role in health maintenance, however, in recent years, it has been said that dysbiosis is increasing among Japanese people due to changes in eating habits or greater social stress. In general, sending living lactic acid bacteria to the intestine is thought to be an efficient way of improving dysbiosis, and some lactic acid bacteria, commonly known as plant- origin lactic acid bacteria, are expected to withstand the harsh environment of the digestive tract and reach the intestines. In this study, we investigated the effect of long-term intake of the supplement MP-1, which contains lactic acid bacteria isolated from the Tonewase persimmon, on the intestinal flora of mice. The mice were divided into three groups. The MP-1 and control groups were respectively fed tablets with and without MP-1 together with a regular diet, and the remaining group was fed only a regular diet for 28 days. In the fecal flora of the MP-1 group, lactic acid bacteria that were not detected before the experiment were detected on day 28. On the other hand, no significant changes were observed in fecal flora of the control and regular diet groups. Therefore, we concluded that long-term intake of MP-1, a supplement containing lactic acid bacteria isolated from the Tonewase persimmon, had a notable effect on their intestinal flora.